COMPARISON OF ZIEHL-NEELSEN BASED LIGHT MICROSCOPY WITH LED FLUORESCENT MICROSCOPY FOR TUBERCULOSIS DIAGNOSIS: AN INSIGHT FROM A LIMITED RESOURCE-HIGH BURDEN SETTING - Noori, Muhammad Yahya; Ali, Faiza; Ali, Zaheer; Sharafat, Shaheen (Journal of Ayub Medical College Abbottabad, 2017)
Background: Microscopy is the most widely used tool for Tuberculosis screening. Conventionally, Ziehl-Neelsen (ZN) staining has been the widely used for staining Acid-Fast Bacilli (AFB) but with the advent of Fluorescent staining, Auramine O stain is now being adapted as the preferred method for setups with high workload as it has the advantage of being less laborious, since bacteria fluoresce in front of a dark background and are easier to count. This study was performed to compare the efficiency of the two methods in a high-burden, limited resource setting to see the magnitude of diagnostic accuracy between ZN and Fluorescent Microscopy, using culture as the standard. Methods: Altogether 987 culturally confirmed cases were considered from the period 36 months during January 2011 to December 2013 and data were compiled from the records maintained at the Provincial Tuberculosis Reference Laboratory at Ojha Institute of Chest Diseases, Dow University of Health Sciences, Karachi. The results from 523 cases examined using ZN and 464 cases using Fluorescent staining method were compared for diagnostic accuracy on the basis of Mycobacterial culture results. Smears are prepared from the clinical samples obtained from presumptive tuberculosis patients. Results: The results of ZN method showed 94.23% [95% CI 91.32-96.39%] sensitivity and 84.91% [95% CI 78.38-90.08%] specificity. While FM showed a sensitivity of 97.15% [95% CI 94.82-98.63%] and specificity of 83.19% [95% CI 74.99-89.56%]. Conclusions: The results showed that Fluorescent microscopy was slightly more sensitive than ZN light Microscopy, while specificity of both the methods were comparable. Keywords: Mycobacterium tuberculosis, Acid fast bacilli, Tuberculosis, Ziehl-Neelsen (ZN) staining, Auramine O Fluorescent staining